Amyloid and tau burden relate to longitudinal changes in the performance of complex everyday activities among cognitively unimpaired older adults: results from the performance-based Harvard Automated Phone Task - Dubbelman, Mark A.; Diez, Ibai; Gonzalez, Christopher; Amariglio, Rebecca E.; Becker, J. Alex; Chhatwal, Jasmeer P.; Gatchel, Jennifer R.; Johnson, Keith A.; Locascio, Joseph J.; Udeogu, Onyinye J.; Wang, Sharon; Papp, Kathryn V.; et al. (Frontiers in Aging Neuroscience, 2024)
Background: Changes in everyday functioning constitute a clinically meaningful outcome, even in the early stages of Alzheimer's disease. Performance-based assessments of everyday functioning might help uncover these early changes. We aimed to investigate how changes over time in everyday functioning relate to tau and amyloid in cognitively unimpaired older adults.Methods: Seventy-six cognitively unimpaired participants (72 ± 6 years old, 61% female) completed multiple Harvard Automated Phone Task (APT) assessments over 2.0 ± 0.9 years. The Harvard APT consists of three tasks, performed through an automated phone system, in which participants refill a prescription (APT-Script), select a new primary care physician (APT-PCP), and transfer money to pay a bill (APT-Bank). Participants underwent Pittsburgh compound-B and flortaucipir positron emission tomography scans at baseline. We computed distribution volume ratios for a cortical amyloid aggregate and standardized uptake volume ratios for medial temporal and neocortical tau regions. In separate linear mixed models, baseline amyloid by time and tau by time interactions were used to predict longitudinal changes in performance on the Harvard APT tasks. Three-way amyloid by tau by time interactions were also investigated. Lastly, we examined associations between tau and change in Harvard APT scores in exploratory voxel-wise wholebrain analyses. All models were adjusted for age, sex, and education.Results: Amyloid (unstandardized partial regression coefficient estimate (β) = -0.007, 95% confidence interval (95%CI) = [-0.013, -0.001]), and medial temporal tau (β = -0.013, 95%CI = [-0.022, -0.004]) were associated with change over time in years on APT-PCP only, i.e., higher baseline amyloid and higher baseline tau were associated with steeper rate of decline of APT-PCP.Voxel-wise analyses showed widespread associations between tau and change in APT-PCP scores over time.Even among cognitively unimpaired older adults, changes over time in the performance of cognitively complex everyday activities relate to cortical amyloid and widespread cerebral tau burden at baseline. These findings support the link between Alzheimer's disease pathology and function and highlight the importance of measuring everyday functioning in preclinical disease stages.